Treatment of the oily produced water (OPW) using coagulant mixtures - R. Hosny; M. Fathy; M. Ramzi; Th. Abdel Moghny; S.E.M. Desouky; S.A. Shama (Egyptian Journal of Petroleum)
Treatment of the oily produced water (OPW) before injection into oil reservoirs is necessary to reduce formation damage. This can be done using chemo-physical process to minimize the oil droplets in water. In this respect, this work aims to extract natural polymer (chitosan) from shrimp shells and mix it with coagulants (chitosan/carboxy methyl cellulose and chitosan/aluminum sulfate) to adsorb oil from OPW. Adsorption experiments were carried out in batch mode firstly to choose the best coagulants in water treatment, also to investigate the effects of pH on the adsorption uptake, adsorbent dosage, coagulant mixture doses and contact time. It was found that the oil removal by chitosan reached 96.35% and 59% at pH = 4 and pH = 9, respectively. The ability of chitosan to remove oil was increased after adding different coagulants CMC/or aluminum sulfate at average mixing time between 30 and 60 min. It was also found that the highest removal efficiency of chitosan/CMC is 99% at (90% chitosan: 10% CMC) and chitosan/Al2(SO4)3 is 85% at (80% chitosan: 20% Al2(SO4)3). The SEM photographs of chitosan, chitosan/CMC and chitosan/Al2(SO4)3 mixture as oil removal showed that chitosan/Al2(SO4)3 lies between chitosan alone and chitosan/CMC mixture. Generally chitosan/CMC characterized significantly by its high ability to adsorb petroleum oil and suspended solids from OPW, additionally, reduces the economic cost of water treatment.